1998
DOI: 10.1103/physrevlett.81.1098
|View full text |Cite
|
Sign up to set email alerts
|

Spin Liquid in the Multiple-Spin Exchange Model on the Triangular Lattice: 3He on Graphite

Abstract: Using exact diagonalizations, we investigate the T = 0 phase diagram of the Multi-Spin Exchange (MSE) model on the triangular lattice: we find a transition separating a ferromagnetic phase from a non-magnetic gapped Spin Liquid phase. Systems far enough from the ferromagnetic transition have a metamagnetic behavior with magnetization plateaus at m/msat = 0 and 1/2. The MSE has been proposed to describe solid 3 He films adsorbed onto graphite, thus we compute the MSE heat capacity for parameters in the low dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
171
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(176 citation statements)
references
References 27 publications
5
171
0
Order By: Relevance
“…7 While extensive studies on frustrated magnets have revealed that the triangular HAF may exhibit the magnetic LRO, 8,9,10,11,12,13,14,15,16,17,18 the Anderson's idea is still attracting much interest, and has been tested for its possible realization in other geometrically frustrated systems such as pyrochlore and Kagome HAF, and multiple ring exchange spin models. 19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 Recently, Shimizu et al reported that in an organic Mott insulator with spin s = 1/2 on a triangular lattice, κ-(ET) 2 Cu 2 (CN) 3 , no magnetic LRO is observed down to 32 mK. 36 Their experimental results suggest the possibility of a new kind of a ground state including the spin liquid.…”
mentioning
confidence: 99%
“…7 While extensive studies on frustrated magnets have revealed that the triangular HAF may exhibit the magnetic LRO, 8,9,10,11,12,13,14,15,16,17,18 the Anderson's idea is still attracting much interest, and has been tested for its possible realization in other geometrically frustrated systems such as pyrochlore and Kagome HAF, and multiple ring exchange spin models. 19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 Recently, Shimizu et al reported that in an organic Mott insulator with spin s = 1/2 on a triangular lattice, κ-(ET) 2 Cu 2 (CN) 3 , no magnetic LRO is observed down to 32 mK. 36 Their experimental results suggest the possibility of a new kind of a ground state including the spin liquid.…”
mentioning
confidence: 99%
“…solid 3 He; for an extensive review of magnetism in solid 3 He, see Roger [35] and references therein. Since the early studies by Thouless [36], single monolayers of solid 3 He have been absorbed on graphite [37,38] and several studies were performed to develop a theoretical understanding of the experiments in terms of multiple spin-exchange models [39][40][41][42][43][44][45][46][47]. Additionally, multiple spin-exchange models have gained interest in frustrated spin systems, in particular the parent cuprate high-temperature superconductors [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…1͒ and in the quasi-1D spin-ladder compound La 6 Ca 8 Cu 24 O 41 , 2 as well as two-magnon Ramanscattering measurements on doped systems related to the latter 3 indicate the presence of contributions from a four-spin cyclic exchange interaction on the order of 10-20 % of the nearest-neighbor superexchange. Measurements of the magnetization and heat capacity of 3 He films of various fillings adsorbed on graphite surfaces 4,5 have been interpreted 6 in terms of cyclic three-, four-and higher-spin-exchange processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations of the influence of this interaction on physical properties have employed perturbative approaches, 9,10 spin-wave analysis, 11,12 numerical exact diagonalization of small clusters, 6 exact diagonalization in combination with conformal field theory ͑CFT͒, 13 and the density-matrix renormalization-group ͑DMRG͒ technique. 14 -17 The majority of these studies is restricted to the regime of weak ring-exchange coupling and to systems with only a nearest-neighbor Heisenberg superexchange interaction in addition to this term.…”
Section: Introductionmentioning
confidence: 99%